Structural, electronic paramagnetic resonance and magnetic properties of praseodymium-doped rare earth CeO2 semiconductors - Oliveira, L. L. [UNESP]; Cortés, J. A. [UNESP]; Caldeira, B. S. [UNESP]; Strusch, T.; Wiedwald, U.; Simoes, A. Z. [UNESP] (Elsevier, 2021)
In this work, praseodymium (Pr) doped cerium oxide (CeO2) was prepared using the microwave-assisted hydrothermal method (MAH) and the properties were investigated by X-ray diffraction analysis (XRD), Raman spectroscopy, Field Emission Gun Scanning Electron Microscope (FEG-SEM), BET method, Photoluminescence spectroscopy (PL), Fourier-transform infrared spectroscopy (FTIR), Ultraviolet–visible spectroscopy (UV–Vis), Electron paramagnetic resonance spectroscopy (EPR) and Magnetometry. The results showed that increasing the Pr-doping promotes a structural disorder due to increased oxygen vacancies. XRD confirmed a cubic structure without deleterious phases with modifications in the structure caused by alteration in the cerium oxidation state as well as changes in the crystallite size and strain obtained by Wellinson-Hall method. Raman spectroscopy shows that changing the Pr content results in samples with different defect densities at short range. FEG-SEM showed that the nanocrystals are agglomerated with small particles tend to aggregate spontaneously to decrease the surface energy. BET method showed that the Pr doping results in a gain of specific surface area. PL indicated that Pr3+ leads to distinct emissions; red emission associated to oxygen vacancies located near the conduction band (shallow defects), green emission associated to electron-hole recombination and orange emission associated to shallow defects and electron-hole recombination. FTIR indicated the complete process of nucleation with no other phase. UV–Vis showed the transitions between oxygen 2p, cerium 4f and praseodymium 4f states. The EPR signal shows events occurring around 344 mT. These events can be related due the presence of paramagnetic elements containing unpaired electrons, such as Ce (III), which is indicative of cerium reduction caused by Pr ions, as evidenced by Rietveld data. Regardless of the Pr concentration used in this research, the magnetic measurements show a superparamagnetic system below the blocking temperature of ~20 K and a paramagnetic system above this temperature, which indicates no significant changes in the average size of the nanoparticles. Surface area, crystallite size and the temperature are important parameters, which control the magnetic properties of such N-type semiconductors.
Keywords: CeO2 semiconductors; Hydrothermal synthesis; Microwave irradiation; Praseodymium-doped